2021
DOI: 10.1186/s12870-021-03269-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide characterization and functional analysis of Xyloglucan endo-transglycosylase/hydrolase (XTH) gene family of Salicornia europaea L. under salinity and drought stress

Abstract: Background Salicornia europaea is a halophyte that has a very pronounced salt tolerance. As a cell wall manipulating enzyme, xyloglucan endotransglycosylase/hydrolase (XTH) plays an important role in plant resistance to abiotic stress. However, no systematic study of the XTH gene family in S. europaea is well known. PacBio Iso-Seq transcriptome sequence data were used for bioinformatics and gene expression analysis using real-time quantitative polymerase chain reaction (RT-qPCR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…Thus far, the XTH family has been identified and analyzed in species such as Arabidopsis thaliana (33), Hordeum vulgare (24), Glycine max (61), and Nicotiana tabacum (54). ( Nomchit et al, 2010 ; Li et al, 2018 ; Meng et al, 2018 ; Cheng et al, 2021 ; Strohmeier et al, 2004 ; Tiika et al, 2021 ). The XTH family was initially classified into three groups, named groups I, II, and III, in Arabidopsis ( Campbell & Braam, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, the XTH family has been identified and analyzed in species such as Arabidopsis thaliana (33), Hordeum vulgare (24), Glycine max (61), and Nicotiana tabacum (54). ( Nomchit et al, 2010 ; Li et al, 2018 ; Meng et al, 2018 ; Cheng et al, 2021 ; Strohmeier et al, 2004 ; Tiika et al, 2021 ). The XTH family was initially classified into three groups, named groups I, II, and III, in Arabidopsis ( Campbell & Braam, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has revealed that XTHs are instrumental for coping with abiotic stresses through cell remodeling and enhanced cell wall biogenesis in plants ( Eklof & Brumer, 2010 ; Tiika et al, 2021 ). For instance, the constitutive expression of CaXTH3 has been verified to enhance resistance to salinity and drought stress in tomato plants ( Choi et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…We downloaded the transcriptome sequence of S. europaea from the NCBI database ( https://www.ncbi.nlm.nih.gov/sra ) (Accession number: PRJNA725943 ) ( Tiika et al, 2021 ). Keywords related to potassium transport proteins were used to search candidate SeKUPs in S. europaea based on the transcriptome database.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we identified SeKUPs in S. europaea using PacBio sequencing system data ( Tiika et al, 2021 ). We thoroughly performed multiple sequence alignment, presence of conserved motifs in the proteins, phylogenetic analysis, and real-time quantitative polymerase chain reaction (RT-qPCR) of SeKUPs in different tissues of S. europaea in response to salinity and K + deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Xyloglucan endotransglycosylase/hydrolase (XTH) enzymes play a role in the loosening of cell walls and affect cell proliferation. It is involved in plant growth and resistance to stress [47]. We found 24 DEGs were involved in XTH, and XTH 13 was signi cantly up-regulated in TX9425 under waterlogging stress (Table S4).…”
Section: Responses Of Ros and Hormonal To Waterloggingmentioning
confidence: 95%